Magnetic Nanoparticle-Based Ligand Replacement Strategy for Chemical Luminescence Determination of Cholesterol - Wu, Yalan; Peng, Danfeng; Qi, Zhiwen; Zhao, Jing; Huang, Wenyi; Zhang, Ying; Liu, Changhui; Deng, Tao; Liu, Fang (Frontiers in Chemistry, 2020)
Determination of serum cholesterol (Chol) is important for disease diagnosis, and has attracted great attention during the last few decades. Herein, a new magnetic nanoparticle-based ligand replacement strategy has been presented for chemical luminescence detection of Chol. The detection depends on ligand replacement from ferrocene (Fc) to Chol through a β-cyclodextrin (β-CD)–based host–guest interaction, which releases Fc–Hemin as a catalyst for the luminol/hydrogen peroxide chemical luminescence system. More importantly, the luminescence signal can be captured by the camera of a smartphone, thus realizing Chol detection with less instrument dependency. The limit of detection of this method is calculated to be 0.18 μM, which is comparable to some of the developed methods. Moreover, this method has been used successfully to quantify Chol from serum samples with a simple extraction process.